Effects of educational resources on mathematical achievements of Turkish students: Findings from PISA 2006 - Demir, Ibrahim (SILA SCIENCE, 2012)
Interaction among teacher, student and educational sources are the cornerstones of learning concept. Therefore, our purpose was to investigate relationship between students' mathematics achievement and educational resources. The data consisted of 4942 15 year-old Turkish students who participated in PISA in Turkey. Analysis was done with hierarchical linear model. These clustered data set with a two level hierarchical structure examined students nested within different schools. Two-level model was used to estimate coefficients and modeled differences across schools. Results from this study indicated that higher economic social and cultural status and the students who have more educational material at home had significantly positive effects on mathematics achievement. The sufficiency of educational resources at school also has positive affect on mathematics achievement. When reference group was taken general high school, students from Science High School or Anatolian High School had significant differences.
Keywords: Hierarchical linear model; Educational resources at home and school; School types; Mathematics achievement; PISA; TEACHERS; SCIENCE; CHEMISTRY; Education & Educational Research